A chat about insurance: Experimental results from rural Bangladesh - Clarke, Daniel J.; de Nicola, Francesca; Hill, Ruth Vargas; Kumar, Neha; Mehta, Parendi (Wiley, 2015)
Farmers throughout the developing world face multiple sources of uninsured risk to agricultural production and household assets. In this paper, we present results from an experimental demand‐elicitation exercise in rural Bangladesh to shed light on smallholder farmers' interest in formal insurance products. We propose a suite of insurance and savings products, and we randomly vary the price of one insurance option (area‐yield insurance) and the presence of one of the savings options (group savings). Consistent with economic theory, farmers buy more of the insurance products that cover the risks they primarily face. However, because farmers are subject to a variety of risks, they do not focus on only one type of insurance; instead, they evenly split their endowment between life and disability insurance and agricultural insurance. Demand for area‐yield insurance falls with price; we also observe important cross‐price elasticities with other insurance products. The presence of group savings does not alter demand for insurance, though group savings is found to be a particularly popular risk management tool, especially when decisions are made in groups.